Role of chaihu yujin decoction in cholecystitis: a systematic investigation integrating multi-omics and experimental validation - Feng Xu; Jia-Han Xu; Xiao-Min Chen; Kai-Li Mao; Jie Hu; Hong-Liang Zheng; Huan-Huan Xia; Zhi-Hui Zhang; Qiu-Ting Lin (Functional & Integrative Genomics, 2026)

Substitution of solid fats in model baked foods using emulsion-templated oleogels: Effects on microstructure, texture, and flavor - Junqing Han; Wenbo Miao; Qianzhu Lin; David Julian McClements; Keyu Lu; Zhengyu Jin; Zhitao Li; Chao Qiu (Food Bioscience, 2026)

A 300-year anthropogenic record of sterol biomarkers in sediments from mangrove wetland, Dongzhai Harbor, Hainan Island, South China - Gaoen Wu; Jianjun Wang; Xihuang Lin; Yuhong Wang; Wu Men; Liqiang Xu; Xiuhua Yan; Shihua Han; Guangle Qiu; Manyu Kang; Shuh-Ji Kao (Estuarine, Coastal and Shelf Science, 2026)

Multichannel epicardial bioelectronics via a stretchable, wet-adhesive, antibacterial hydrogel with highly conformable Interface - Si Shen; Xingyun Fan; Weibin Liang; Chenghua Xie; Nian Zhang; Pengqi Wang; Rurong Lin; Jie Zhang; Yanni Han; Chongyin Qiu; Shiqi Guo; Jingxing Dai; et al. (Chemical Engineering Journal, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Bioaccumulation of rare earth elements (REEs) and trace metals in corals of the South China Sea - Yao-Wen Qiu; Han-Lin Qiu (Marine Chemistry, 2026)

The light side of the microbiome in trauma: Mechanism and applications - Han-Yue Luo; Lei-Ming Cao; Kan Zhou; Yi-Fu Yu; Yao Xiao; Guang-Rui Wang; Bing Liu; Qiu-Ji Wu; Xiao-Long Wang; Zhi-Yong Song; Lin-Lin Bu (Chemical Engineering Journal, 2026)

Effects of biochar and NPK fertilization on growth, root traits, and physiological performance of Casuarina equisetifolia seedlings - Bin Xie; Lin Zhao; Qiping Qiu; Han Lin; Can Chen; Anqiang Xie; Chuanyang Jiang; Zichuan Chen (Journal of Soils and Sediments, 2026)

Co-occurrence and regulation of nanoplastics and typical flame retardant in anammox process: Potential risk and molecular mechanism - Jing-Ao Jin; Na-Na Han; Wei-Lin Guo; Qiu-You Xu; Jiao-Jiao Wang; Nian-Si Fan; Ren-Cun Jin (Journal of Water Process Engineering, 2026)

Preparation-controlled structural modulation of starch nanoparticles and protein corona formation mechanisms - Han Hu; David Julian McClements; Qianzhu Lin; Hangyan Ji; Zhengyu Jin; Chao Qiu (Food Hydrocolloids, 2026)

Biochar-NPK interactions improve soil nutrients and enzyme activity in Casuarina equisetifolia - Qiping Qiu; Bin Xie; Lin Zhao; Han Lin; Anqiang Xie; Dongyang Wu; Can Chen (Journal of Soils and Sediments, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Bio-inspired rigid-Soft interaction for robust picking underwater - Shuqiao Zhong; Wanghongjie Qiu; Xudong Han; Chaoyang Song; Zhiyuan Zhou; Fang Wan; Jian Lin (Ocean Engineering, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Shen-Ling-Bai-Zhu-San alleviates ulcerative colitis by enhancing mitophagy via the Nrf2/PINK1/Parkin pathway - Huan Wang; Jian Han; Lin Li; Yan Li; Jun Yang; Wangzhong Qiu; Liuhua Yao; Jianjun Zhou (Journal of Molecular Histology, 2026)

The glutamyl-prolyl-tRNA synthetase 1 inhibitor halofuginone exerts synergistic antitumor effects with bortezomib in colon cancer cells - Han Lin; Ying Yan; Chenyu Qiu; Junqi Wang; Wenying Fu; Chongchong Shu; Yinghua Chen; Chenxin Xu; Shaotang Li; Yiqun Xia; Jundixia Chen; Yunzhi Chen; et al. (Toxicology and Applied Pharmacology, 2026)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Microplastic contamination in waterbirds and their habitats: evidence from little egrets (Egretta garzetta) in tropical rice fields - Han-xun Qiu; Chuan-biao Xu; Xin Huang; Xiang-yin Wei; Zi-lin Pang; Lan-fang Du; Li Jiang; Ji-liang Zhang (Environmental Research, 2025)

Formoterol, a clinically approved drug, inhibits ferroptosis by suppressing lipid peroxidation and attenuates APAP-induced acute liver injury - Lin-Song Teng; Zhen-Dong Ying; Xiao-Han Sun; Hao-Cheng Hou; Shi-Dong Qiu; Peng Liu; Ke-Jing Li; Lei Zhang; Xie-Huang Sheng (Chemico-Biological Interactions, 2025)

Utilizing UAV-based high-throughput phenotyping and machine learning to evaluate drought resistance in wheat germplasm - Xiaojing Zhu; Xin Liu; Qian Wu; Mengshi Liu; Xueli Hu; Hui Deng; Yun Zhang; Yunfeng Qu; Baoqi Wang; Xiaoman Gou; Qiongge Li; Changsheng Han; et al. (Computers and Electronics in Agriculture, 2025)

Crystallization regulation and defect passivation of perovskite films via resonance-structured ionic additive for high-performance solar cells - Guogen Huang; Yuqing Dong; Guanlin Li; Zebing Gao; Chuanlin Gao; Kangbo Sun; Haoxuan Zeng; Haohua Wu; Jinxing He; Xinting Wang; Qing Bai; Tong Shan; et al. (Chemical Engineering Journal, 2025)

Characterizing Gray matter atrophy patterns associated with accelerometer-measured sedentary behavior: a population-based study - Minle Tian; Xiaolei Han; Ming Mao; Xiaomeng Li; Yi Dong; Jiahao Ding; Qinghua Zhang; Shi Tang; Xiaojuan Han; Lin Song; Tingting Hou; Lin Cong; et al. (Brain Imaging and Behavior, 2025)
Evidence has linked self-reported sedentary behaviors with dementia and cognitive impairment; however, the underlying mechanisms remain poorly understood. We investigated the associations of accelerometer-measured sedentary behavior patterns with gray matter atrophy patterns in rural-dwelling older adults, while taking into account the manner in which sedentary time is accrued (in short or long bouts). This community-based study involved 911 dementia-free older adults (age ≥ 60 years, 59% women) who participated in both ActiGraph and brain MRI substudies within MIND-China (2018–2020). Sedentary behavior parameters (total sedentary time, mean sedentary bout duration, and sedentary breaks) were recorded with accelerometers. Regional gray matter volumes (GMV) were measured using voxel-based morphometry (VBM) methods. Data were analyzed using the general linear regression models, restricted cubic spline curves, and VBM analysis. There was an inverted U-shaped association between daily sedentary time and GMV in temporal, cingulate, and medial temporal cortex, while longer mean sedentary bout duration was linearly related to decreased GMV in total, frontal, temporal, insula, cingulate, and medial temporal cortex. Greater daily time spent in light or moderate-to-vigorous physical activity (LPA and MVPA) was correlated with larger insula GMV. The VBM analysis suggested that prolonged daily total sedentary time and mean sedentary bout duration were significantly associated with smaller GMV in extensive brain regions, especially in thalamus and insula. In conclusion, gray matter atrophy associated with sedentary behavior in older adults is characterized by reduced GMV in global, frontal, temporal, medial temporal, and cingulate cortex, especially in the insula and thalamus regions.

Xanthine oxidase inhibitory constituents from the roots of Ampelopsis japonica - Yu-Lin Li; Fen Liu; Li-Yun Zhao; Han-Xiang Li; Aikebaier Jumai; Zhi-Fang Xu; Sheng-Xiang Qiu (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Dietary vitamin C improves muscle hardness and springiness associated with collagen and elastin synthesis in grass carp (Ctenopharyngodon idella) - Xin-Lei Xue; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Yang Liu; Yao-Bin Ma; Jun Jiang; Dong Han; Wen-Bin Zhang; Wei-Dan Jiang (Food Research International, 2025)

Exploring exhaled volatile organic compounds as potential biomarkers in anti-MDA5 antibody-positive interstitial lung disease - Yuxuan Wang; Xuewen Wang; Luqin Yang; Ke Wang; Fengqin Zhang; Huihui Yue; Junqi Wang; Minhua Peng; Pengnan Fan; Xiangcheng Qiu; Han Zhang; Wei Lin; et al. (Molecular and Cellular Biochemistry, 2025)

The heterogeneous response in leaf traits among seasons and plant types of an evergreen broadleaf forest in western China to nitrogen addition was regulated by fertilization intensity - Wenzheng Chang; Qiu Song; Tianxing Liang; Jie Chen; Lixia Wang; Han Li; Li Zhang; Chengming You; Hongwei Xu; Lin Xu; Bo Tan; Zhenfeng Xu; et al. (Plant and Soil, 2025)

Unprecedented short-circuit current density and efficiency of vacuum-deposited organic solar cells based on 8H-thieno[2′,3′:4,5]thieno[3,2-b] thieno[2,3-d]pyrrole - Bin-Wen Chen; Ming-Wei An; Kang Wang; Sang Young Jeong; Xu Wang; Zhen-Lin Qiu; Kun Cao; Shan-Yu Zheng; Lu Wang; Han Young Woo; Da-Qin Yun; Lin-Long Deng; et al. (Science Bulletin, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Enhancing electrochemical reductive defluorination of PFASs using ZIF-67 modified cathode: Mechanistic insights and performance optimization - Xing Zhang; Han Wu; Yue Wang; Yafei Wang; Yangyang Deng; Yanping Zhu; Shengsen Zhang; Huub Rijnaarts; Harry Bruning; Junhao Qin; Qingqi Lin; Zhuobiao Ni; et al. (Water Research, 2025)

Recent advances in natural gums as additives to help the construction and application of edible biopolymer gels: the example of hydrogels and oleogels - Wenbo Miao; Han Jiang; Xiaojing Li; Shangyuan Sang; Liming Jiang; Qianzhu Lin; Zhiheng Zhang; Long Chen; Jie Long; Aiquan Jiao; Jinpeng Wang; Zhengyu Jin; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Risk hotspots and influencing factors identification of heavy metal(loid)s in agricultural soils using spatial bivariate analysis and random forest - Xiaohang Xu; Zhidong Xu; Longchao Liang; Jialiang Han; Gaoen Wu; Qinhui Lu; Lin Liu; Pan Li; Qiao Han; Le Wang; Sensen Zhang; Yanhai Hu; et al. (Science of The Total Environment, 2024)

Unraveling the effects of prenatal anesthesia on neurodevelopment: A review of current evidence and future directions - Qiu-Xia Xiao; Min-Jian Geng; Qiu-Lin Wang; Chang-Le Fang; Jing-Han Zhang; Qi Liu; Liu-Lin Xiong (NeuroToxicology, 2024)

Lipid fingerprinting and geographical origin identification of large yellow croaker (Larimichthys crocea) using UHPLC-QTOF-MS - Haolei Han; Xiangxin Lin; Yuxuan Wu; Houru Li; Qi Jia; Changmin Hu; Yixuan Lin; Guangqin Liao; Yongzhong Qian; Jing Qiu (Food Research International, 2024)

The influences of ApoE isoforms on endothelial adherens junctions and actin cytoskeleton responding to mCRP - Zhengrong Zhang; Weiwei Lin; Qini Gan; Maohua Lei; Bin Gong; Chao Zhang; Jessica Salles Henrique; Jingyan Han; Hua Tian; Qiushan Tao; Lawrence A. Potempa; Thor D. Stein; et al. (Angiogenesis, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Recent advances in the application of starch derivatives in baked foods: Effects on quality and functionality - Han Hu; Qianzhu Lin; David Julian McClements; Hangyan Ji; Zhengyu Jin; Chao Qiu (Trends in Food Science & Technology, 2024)

Farmland’s silent threat: Comprehensive multimedia assessment of micropollutants through non-targeted screening and targeted analysis in agricultural systems - Yang Qiu; Lijun Liu; Caifei Xu; Bo Zhao; Hang Lin; He Liu; Weixuan Xian; Han Yang; Rui Wang; Xingjian Yang (Journal of Hazardous Materials, 2024)

Fabrication and characterization of polydopamine-mediated zein-based nanoparticle for delivery of bioactive molecules - Zhiheng Zhang; Han Jiang; Guo Chen; Wenbo Miao; Qianzhu Lin; Shangyuan Sang; David Julian McClements; Aiquan Jiao; Zhengyu Jin; Jinpeng Wang; Chao Qiu (Food Chemistry, 2024)

Regional-scale biogeographical patterns of soil extracellular enzyme activities across eight Chinese fir plantation locations - Han-shuo Zhang; Mi-lin Deng; Hao Yang; Bi-jiang Fang; Wen-feng Lan; Qiu-hua Ma; Huai-feng Weng; Zhi-jie Yang; Yi-rong Zhang; Yong Zheng (European Journal of Soil Biology, 2024)

Encapsulation and protection of β-carotene in Pickering emulsions stabilized by chitosan-phytic acid-cyclodextrin nanoparticles - Qianzhu Lin; Han Jiang; Xiaojing Li; David Julian McClements; Shangyuan Sang; Jinpeng Wang; Aiquan Jiao; Zhengyu Jin; Chao Qiu (Food Bioscience, 2024)

Self-assembled C-Ag hybrid nanoparticle on nanoporous GaN enabled ultra-high enhancement factor SERS sensor for sensitive thiram detection - Hongpeng Zhou; Jiaoyan Qiu; Yunhong Zhang; Yanbo Liang; Lin Han; Yu Zhang (Journal of Hazardous Materials, 2024)

Spartina alterniflora invasion altered phosphorus retention and microbial phosphate solubilization of the Minjiang estuary wetland in southeastern China - Yan-Zhen Lin; Qi-Qi Chen; Yi-Fan Qiu; Rong-Rong Xie; Hong Zhang; Yong Zhang; Jia-Bing Li; Yong-He Han (Journal of Environmental Management, 2024)

Fabrication of starch-based oleogels using capillary bridges: Potential for application as edible inks in 3D food printing - Wenbo Miao; Yijie Fu; Zhiheng Zhang; Qianzhu Lin; Xiaojing Li; Shangyuan Sang; David Julian McClements; Han Jiang; Hangyan Ji; Chao Qiu; Zhengyu Jin (Food Hydrocolloids, 2024)

Efficient EVs separation and detection by an alumina-nanochannel-array-membrane integrated microfluidic chip and an antibody barcode biochip - Jiaoyan Qiu; Qindong Guo; Yujin Chu; Chunhua Wang; Hao Xue; Yu Zhang; Hong Liu; Gang Li; Lin Han (Analytica Chimica Acta, 2024)

Recent advances in the formation and identification of nanoparticle protein coronas and their effects on the digestion and absorption of polyphenols - Zhiheng Zhang; Han Jiang; Wenbo Miao; Qianzhu Lin; Xiaojing Li; Shangyuan Sang; David Julian McClements; Aiquan Jiao; Zhengyu Jin; Chao Qiu (Trends in Food Science & Technology, 2024)

Inhibitory mechanism of esculetin on tyrosinase and browning of fresh-cut apple: New perspectives - Lin-Jun Wang; Qiu-Han Bai; Qiu-Xia Pan; Yi-Feng Wu; Ting-Ting Shao; Yi-Wen Guo; Wen-Shuang Wei; Yi-Ting Wen; Wei-Ming Chai (Postharvest Biology and Technology, 2024)

Effects of Aegilops longissima chromosome 1Sl on wheat bread-making quality in two types of translocation lines - Yuliang Qiu; Zhiyang Han; Ningtao Liu; Mei Yu; Shuangxi Zhang; Haiqiang Chen; Huali Tang; Zhiyong Zhao; Ke Wang; Zhishan Lin; Fangpu Han; Xingguo Ye (Theoretical and Applied Genetics, 2024)

Discovery and verification of bitter components in Panax notoginseng based on the integrated strategy of pharmacophore model, system separation and bitter tracing technology - Jing Yang; Min Qiu; Tai Lu; Shangdong Yang; Ji Yu; Junzhi Lin; Hongyan Ma; Zhiping Guo; Zhencai Chen; Xue Han; Dingkun Zhang (Food Chemistry, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Enhanced dual-mode electrochemical zinc ion sensing by electric field-driven bi-directional mass transport - Yuzhen Huang; Kai Zhang; Xiaoshuang Chen; Xiaohui Yan; Jiaoyan Qiu; Yu Zhang; Lin Han (Chemical Engineering Journal, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

A novel diagnostic signature of circulating tsRNAs and miRNAs in esophageal squamous cell carcinoma detected with a microfluidic platform - Di Huang; Yujin Chu; Jiaoyan Qiu; Xiaoshuang Chen; Junhua Zhao; Yu Zhang; Shunjia Li; Yufeng Cheng; Han Shi; Lin Han; Jianbo Wang (Analytica Chimica Acta, 2023)

2,3′,4,4′,5-Pentachlorobiphenyl induces mitochondria-dependent apoptosis mediated by AhR/Cyp1a1 in mouse germ cells - Qiu-Yue Wang; Lin Zhang; Xiao-Ying Han; Dong-Mei Wang; Ming-Long Ding; Dong Cheng; Qi-Long He; Shu-Zhen Liu (Journal of Hazardous Materials, 2023)

A self-assembly hydrophobic oCDs/Ag nanoparticles SERS sensor for ultrasensitive melamine detection in milk - Jiaoyan Qiu; Yujin Chu; Qihang He; Yingkuan Han; Yu Zhang; Lin Han (Food Chemistry, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Reciprocal modulation between cigarette smoking and internet gaming disorder on participation coefficient within functional brain networks - Xianxin Qiu; Xu Han; Yao Wang; Weina Ding; Yawen Sun; Hao Lei; Yan Zhou; Fuchun Lin (Brain Imaging and Behavior, 2022)

Whole brain volume and cortical thickness abnormalities in Wilson’s disease: a clinical correlation study - Yukun Song; Lin Zou; Jing Zhao; Xiangxue Zhou; Yingqian Huang; Haishan Qiu; Haiwei Han; Zhiyun Yang; Xunhua Li; Xiaoying Tang; Jianping Chu (Brain Imaging and Behavior, 2021)

Distributions of Total Mercury and Methylmercury in Dragonflies from a Large, Abandoned Mercury Mining Region in China - Gaoen Wu; Shunlin Tang; Jialiang Han; Chan Li; Lin Liu; Xiaohang Xu; Zhidong Xu; Zhuo Chen; Yajie Wang; Guangle Qiu (Archives of Environmental Contamination and Toxicology, 2021)

Dietary exposure assessment of cadmium, arsenic, and lead in market rice from Sri Lanka - Lin Liu; Jialiang Han; Xiaohang Xu; Zhidong Xu; Kasun S. Abeysinghe; Anjana J. Atapattu; P. Mangala C. S. De Silva; Qinhui Lu; Guangle Qiu (Environmental Science and Pollution Research, 2020)

Anomalous distribution of distinctive water masses over the Carlsberg Ridge in May 2012 - Hailun He; Yuan Wang; Xiqiu Han; Yanzhou Wei; Pengfei Lin; Zhongyan Qiu; Yejian Wang (Ocean Science, 2020)
In May 2012, we conducted a hydrographic survey over the Carlsberg Ridge in the northwest Indian Ocean. In this paper, we use these station data, in combination with some free-floating Argo profiles, to obtain the sectional temperature and salinity fields, and subsequently, the hydrographic characteristics are comprehensively analyzed. Through the basic T–S diagram, three salty water masses, Arabian Sea High-Salinity Water, Persian Gulf Water, and Red Sea Water, are identified. The sectional data show a clear ventilation structure associated with Arabian Sea High-Salinity Water. The 35.8 psu salty water sinks at 6.9∘ N and extends southward to 4.4∘ N at depths around the thermocline, where the thermocline depth is in the range of 100 to 150 m. This salty thermocline extends much further south than climatology indicates. Furthermore, the temperature and salinity data are used to compute the absolute geostrophic current over the specific section, and the results show mesoscale eddy vertical structure different from some widely used oceanic reanalysis data. We also find a west-propagating planetary wave at 6∘ N, and the related features are described in terms of phase speed and horizontal and vertical structures.

NOD1 inhibits proliferation and enhances response to chemotherapy via suppressing SRC-MAPK pathway in hepatocellular carcinoma - Xiaomin Ma; Yumin Qiu; Lihui Zhu; Yunxue Zhao; Yueke Lin; Dapeng Ma; Zhenzhi Qin; Caiyu Sun; Xuecheng Shen; Tao Li; Lihui Han (Journal of Molecular Medicine, 2020)

Spatial Distribution and Congener Profiles of Polybrominated Diphenyl Ethers in Surface Sediment from Sanmen Bay and Xiamen Bay, Southeast China - Kunyan Liu; Yong Qiu; Shanshan Zhou; Kunde Lin; Da Chen; Han Qu; Xiaodong Wang; Yongxia Hu; Yan Wang (Bulletin of Environmental Contamination and Toxicology, 2019)

The impact and mechanism of quaternary ammonium compounds on the transmission of antibiotic resistance genes - Yue Han; Zhen-Chao Zhou; Lin Zhu; Yuan-Yuan Wei; Wan-Qiu Feng; Lan Xu; Yang Liu; Ze-Jun Lin; Xin-Yi Shuai; Zhi-Jian Zhang; Hong Chen (Environmental Science and Pollution Research, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

Predicting the cytotoxicity of disinfection by-products to Chinese hamster ovary by using linear quantitative structure–activity relationship models - Li-Tang Qin; Xin Zhang; Yu-Han Chen; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang; Hua Lin; Dun-Qiu Wang (Environmental Science and Pollution Research, 2019)

l-Carnitine inhibits the senescence-associated secretory phenotype of aging adipose tissue by JNK/p53 pathway - Lian-wei Yang; Ming Song; Yu-lin Li; Ya-peng Liu; Chun Liu; Lu Han; Zhi-hao Wang; Wei Zhang; Yan-qiu Xing; Ming Zhong (Biogerontology, 2019)

Provenance of the Langjiexue Group to the south of the Yarlung-Tsangpo Suture Zone in southeastern Tibet: Insights on the evolution of the Neo-Tethys Ocean in the Late Triassic - Da-Ren Fang; Gen-Hou Wang; Ken-ichiro Hisada; Guo-Li Yuan; Fang-Lin Han; Dian Li; Yu Tang; Qiu-Ming Pei; Liang-Liang Zhang (International Geology Review, 2019)

Bioaccumulation and Cycling of Polycyclic Aromatic Hydrocarbons (PAHs) in Typical Mangrove Wetlands of Hainan Island, South China - Yao-Wen Qiu; Han-Lin Qiu; Jun Li; Gan Zhang (Archives of Environmental Contamination and Toxicology, 2018)

Sumoylation of SUVR2 contributes to its role in transcriptional gene silencing - Yu-Xi Luo; Yong-Feng Han; Qiu-Yuan Zhao; Jin-Lu Du; Kun Dou; Lin Li; She Chen; Xin-Jian He (Science China Life Sciences, 2018)

Development of a stable Japanese encephalitis virus replicon cell line for antiviral screening - Qiu-Yan Zhang; Xiao-Dan Li; Si-Qing Liu; Cheng-Lin Deng; Bo Zhang; Han-Qing Ye (Archives of Virology, 2017)

Anti-Collision Assessment and Prediction Considering Material Corrosion on an Offshore Protective Device - Ang Qiu; Xiangxi Han; Hongyu Qin; Wei Lin; Youhong Tang (Journal of Marine Science and Engineering, 2017)
Corrosion deterioration of steel can heavily degrade the performance of marine and offshore structures. A typical steel protective device, which has worked for a dozen years in a river estuary, is selected as the research object. Its current corrosion response is measured on site and its further corrosive response is predicted based on measurement data and the structure’s current state. Nonlinear finite element method is utilized to analyze the degradation of the protective device’s anti-collision performance. Meanwhile the rubber buffer effect has been investigated for its anti-collision on the protective device. A prediction method is proposed that can accurately forecast degradation of the anti-collision performance of a protective device as time progresses.

PreSurgMapp: a MATLAB Toolbox for Presurgical Mapping of Eloquent Functional Areas Based on Task-Related and Resting-State Functional MRI - Huiyuan Huang; Zhongxiang Ding; Dewang Mao; Jianhua Yuan; Fangmei Zhu; Shuda Chen; Yan Xu; Lin Lou; Xiaoyan Feng; Le Qi; Wusi Qiu; Han Zhang; et al. (Neuroinformatics, 2016)

Wnt5a mediated canonical Wnt signaling pathway activation in orthodontic tooth movement: possible role in the tension force-induced bone formation - Hai-Di Fu; Bei-Ke Wang; Zi-Qiu Wan; Heng Lin; Mao-Lin Chang; Guang-Li Han (Journal of Molecular Histology, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

Enteractinococcus lamae sp. nov. and Enteractinococcus viverrae sp. nov., isolated from animal faeces - Xiu Chen; Gui-Ding Li; Qin-Yuan Li; Cai-Juan Hu; Shu-Mei Qiu; Yi Jiang; Cheng-Lin Jiang; Li Han; Xue-Shi Huang (Antonie van Leeuwenhoek, 2015)

Re-Transurethral Resection Treatment for Non-invasive Bladder Tumor - Cong-hui Han; Zhenduo Shi; Xujun Xuan; Bo Chen; Bingzheng Dong; Lin Hao; Xiangzheng Qiu; Xiangju Zhou; Tian-lin Wu; Dong Liu (Cell Biochemistry and Biophysics, 2014)

Halobellus litoreus sp. nov., a Halophilic Archaeon Isolated from a Chinese Marine Solar Saltern - Mei-Lin Zhao; Xing-Xing Qiu; Wen-Jiao Zhang; Dong Han; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2014)

Haloplanus salinus sp. nov., an extremely halophilic archaeon from a Chinese marine solar saltern - Xing–Xing Qiu; Mei-Lin Zhao; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Archives of Microbiology, 2013)

Halorubrum rubrum sp. nov., an extremely halophilic archaeon from a Chinese salt lake - Xing-Xing Qiu; Mei-Lin Zhao; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Antonie van Leeuwenhoek, 2013)

Abnormal baseline brain activity in patients with HBV-related cirrhosis without overt hepatic encephalopathy revealed by resting-state functional MRI - Xiao-Fei Lv; Min Ye; Lu-Jun Han; Xue-Lin Zhang; Pei-Qiang Cai; Gui-Hua Jiang; Ying-Wei Qiu; Shi-Jun Qiu; Yao-Pan Wu; Kai Liu; Zhen-Yin Liu; Pei-Hong Wu; et al. (Metabolic Brain Disease, 2013)

Halobellus rarus sp. nov., a halophilic archaeon from an inland salt lake of China - Wen-Jiao Zhang; Dong Han; Xing-Xing Qiu; Mei-Lin Zhao; Yun-Zhuang Mou; Heng-Lin Cui; Zheng-Rong Li (Antonie van Leeuwenhoek, 2013)

The Transurethral Seminal Vesiculoscopy in the Diagnosis and Treatment of the Seminal Vesicle Disease - Cong-hui Han; Qing Liang; Bing-zheng Dong; Lin Hao; Tao Fan; Jun-jie Zhang; Wen-da Zhang; Bo Chen; Xiang-zheng Qiu; Xiang-ju Zhou; Chang-song Pei (Cell Biochemistry and Biophysics, 2013)

TFF3 mediated induction of VEGF via hypoxia in human gastric cancer SGC-7901 cells - Bayasi Guleng; Jia Han; Jin-Qiu Yang; Qing-Wen Huang; Jian-Kun Huang; Xiao-Ning Yang; Jing-Jing Liu; Jian-Lin Ren (Molecular Biology Reports, 2012)

Molecular mutations associated with the in vitro passage of virulent porcine reproductive and respiratory syndrome virus - Wei Han; Jia-Jun Wu; Xiao-Yu Deng; Zhen Cao; Xiu-ling Yu; Chuan-Bin Wang; Tie-Zhu Zhao; Nan-Hua Chen; Hong-Hui Hu; Wang Bin; Li-Li Hou; Li-Lin Wang; et al. (Virus Genes, 2009)

Tolerance and accumulation of lead by species of Iris L. - Yu-Lin Han; Su-Zhen Huang; Ji-Guang Gu; Shuo Qiu; Jie-Min Chen (Ecotoxicology, 2008)

Carnivory and active hunting by the planktonic testate amoeba Difflugia tuberspinifera - Bo-Ping Han; Tian Wang; Qiu-Qi Lin; Henri J. Dumont (Hydrobiologia, 2008)